X-Ray Repair Cross Complementing 4 (XRCC4) Gene Expressions as Biomarkers for Detection of Ionizing Radiation Exposure - Ali, Abdulsahib K. (University of Thi-Qar Journal of Science, 2014)
The present study aims at using the gene expression as biomarkers in the identification of the biological effects of low and high doses of ionizing radiation (X-ray) in white mice Mus musculus Balb/C, ages 4-6 weeks, weight 30-40 grams. Seventy- two white mice (36 males and 36 females) were divided into two groups; their whole body was exposed to 5 cGy (rad) and 100 cGy (rad) of X-ray radiation at a dose rate of 200 cGy/min, in addition to the control group. Total RNA was successfully isolated using Trizol method from blood and liver samples of mice after 6, 48 hours and 10 days of exposure to radiation as well as of the control group. The RNA concentration was determined spectrophotometrically by measuring their absorbance using nucleic acid and protein analyzer that dependent on the ratio A260/A280 of the wavelength which lead to the determination of RNA purity, it ranged from 1.79-2.1 in all mice groups. RNA integrity and quality were confirmed by agarose gel electrophoresis.Three bands such as 28s, 18s and 5s appeared in a visible manner. This study involved the reverse transcription (RT) of the RNA for the manufacture of complementary DNA (cDNA) using the polymerase chain reaction (PCR) for investigation on above –mentioned groups of animals. Complementary DNA was used in amplification of genes used in the present study, one type of specialized primers were selected for the gene as X-Ray repair cross complementing group 4 (XRCC4).